2017
DOI: 10.1186/s13049-017-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis in an emergency care setting: a one year prospective study in children and adults

Abstract: BackgroundCurrent data on anaphylaxis is based on retrospective and register based studies. The objective of this study was to describe the epidemiology of anaphylaxis in a 1 year prospective study at the emergency care setting, Odense University Hospital, Denmark (2013–2014).MethodsProspective study at the emergency care setting, Odense University Hospital, Denmark (2013–2014). To identify anaphylaxis cases, records from all patients with clinical suspicion on anaphylaxis or a related diagnosis according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
(65 reference statements)
3
33
0
2
Order By: Relevance
“…since we worked at the tertiary reference centre for diagnostics and immunotherapy for children with allergy to insect venom. However, the majority of the paediatric data including the prospective ones, indicated food as the most common factor triggering anaphylaxis in children [1,3,[14][15][16][17][18]. Nevertheless, the allergy profile in different age groups of our patients corresponded well with the rest of the registry; food allergy was predominant in the preschool group, insect venom was more prevalent in school children.…”
Section: Single Centre Data In Comparison To the Registry Datasupporting
confidence: 52%
“…since we worked at the tertiary reference centre for diagnostics and immunotherapy for children with allergy to insect venom. However, the majority of the paediatric data including the prospective ones, indicated food as the most common factor triggering anaphylaxis in children [1,3,[14][15][16][17][18]. Nevertheless, the allergy profile in different age groups of our patients corresponded well with the rest of the registry; food allergy was predominant in the preschool group, insect venom was more prevalent in school children.…”
Section: Single Centre Data In Comparison To the Registry Datasupporting
confidence: 52%
“…In a prospective study published in 2017, anaphylaxis cases were evaluated from 2013 to 2014. Upon review, in 180 anaphylactic patients identified, 83% received glucocorticoids while only 25% received adrenaline [44]. There is an overall lack of evidence for clear benefit of glucocorticoids, but it is frequently used.…”
Section: Anti-histamines and Glucocorticoidsmentioning
confidence: 99%
“…In a prospective study (APOTECA), 226 patients with suspected anaphylaxis were seen at the Emergency Department (ED), Odense University Hospital (OUH), during 1st of May 2013 through 30th of April 2014 [4 ]. In the study the suspected allergic reaction at the ED was classified according to the EAACI diagnostic criteria for anaphylaxis.…”
Section: Food Venom Unknown Elicitor All Elicitors Prescribed Adrenalmentioning
confidence: 99%